2011
DOI: 10.1007/s13139-011-0099-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Metastasis from Hepatocellular Carcinoma Using 18F-FDG PET/CT and 99mTc-HDP Bone Scintigraphy: Characteristics of Soft Tissue Formation

Abstract: Purpose Bone metastasis from hepatocellular carcinoma (HCC) can present with soft tissue formation, resulting in oncologic emergency. Contrast-enhanced FDG PET/CT and bone scintigraphy were compared to evaluate characteristics of bone metastases with or without soft tissue formation from HCC. Methods Of 4,151 patients with HCC, 263 patients had bone metastases. Eighty-five patients with bone metastasis from HCC underwent contrast-enhanced FDG PET/CT. Fifty-four of the enrolled subjects had recent 99m Tc-HDP bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…One of these studies only contains one case of spinal metastasis which shows a large heterogeneous lobulated destructive soft-tissue invading the posterior elements and adjacent structures (15). Another study reported that 55% (47 out of 85) of HCC patients with spinal metastasis presented with soft tissue formation (17). To our knowledge, however, no study has investigated on specific enhancement pattern of metastatic tumors from HCC, making our study the first to report the possibly specific enhancement pattern.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…One of these studies only contains one case of spinal metastasis which shows a large heterogeneous lobulated destructive soft-tissue invading the posterior elements and adjacent structures (15). Another study reported that 55% (47 out of 85) of HCC patients with spinal metastasis presented with soft tissue formation (17). To our knowledge, however, no study has investigated on specific enhancement pattern of metastatic tumors from HCC, making our study the first to report the possibly specific enhancement pattern.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies on spinal metastases from HCC mostly focused on clinical aspects. There have been few studies including radiologic findings of extrahepatic metastases from HCC (14)(15)(16)(17). One of these studies only contains one case of spinal metastasis which shows a large heterogeneous lobulated destructive soft-tissue invading the posterior elements and adjacent structures (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of hidden lesions can lead to early and/or massive recurrence after RFA, especially in patents with relatively large tumors [ 26 , 27 ]. In addition, insufficient work up for extrahepatic metastasis at the time of initial diagnosis can lead to early extrahepatic recurrence in our patients [ 28 ]. In our study, tumor located within 1 cm of the colon was another risk factor for early massive recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Bone metastases is seen in 6.3% of HCC patients. The most common site of bone metastases is the spine (39%), followed by pelvis (19%) and ribs (14%) [6]. As many as 88.5% of patients with bone metastases from HCC die of liver failure resulting from intrahepatic tumor progression.…”
Section: Discussionmentioning
confidence: 99%